Admissions and deaths in government hospitals due to injury in Malaysia (1999-2002) - Zainal Ariffin Omar; Rosnah Ramly; Muhammad Fadhli Mohd Yusoff (Kuala Lumpur : Ministry of Health Malaysia, 2005)
42